Creative Listening as a Driving Force in Explorations of a Subject Matter - Deltner, Johan (Philosophical Inquiry in Education, 2025)
Listening is a familiar activity in education but has received less interest in the literature than speaking, matching its position in our popular culture, which focuses on freedom of speech and extrovert demeanor. Drawing on John Dewey to understand what characterizes creative listening in educational dialogue, this paper argues that creative listening initiates and prolongs explorations into a subject matter through creative tensions, here described as the interplay between originality and meaningfulness that triggers further inquiries and gives rise to ambivalent experiences within the teacher. Through these tensions, creative listening widens the subject matter and increases the opportunities for teachers and students to connect to the world of the subject matter. To achieve this form of listening, the teacher must artfully navigate the tangle of creative endeavors to facilitate enriched educational experiences for the students. By highlighting creative listening as a subtle but powerful force in educational dialogues, this paper strives to emphasize and expand the role of listening in education, promoting an understanding of the way silent communications aid complex forms of knowing.